Focal point a proven system to simplify your life, double your productivity, and achieve all your goals - Tracy, Brian (AMACOM, 2002)
Outlines the secret of high achievement: knowing how to find one's focal point--the one thing to do, at any given moment, to get the best possible results in each area of one's life. This guide helps readers analyze their lives in seven key areas and shows them how to develop goals and plans in each.